2019
DOI: 10.3390/biom9080356
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Use of α-Lipoic Acid for Therapeutic Purposes

Abstract: α-lipoic acid (ALA, thioctic acid) is an organosulfur component produced from plants, animals, and humans. It has various properties, among them great antioxidant potential and is widely used as a racemic drug for diabetic polyneuropathy-associated pain and paresthesia. Naturally, ALA is located in mitochondria, where it is used as a cofactor for pyruvate dehydrogenase (PDH) and α-ketoglutarate dehydrogenase complexes. Despite its various potentials, ALA therapeutic efficacy is relatively low due to its pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
205
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(215 citation statements)
references
References 128 publications
(158 reference statements)
1
205
0
9
Order By: Relevance
“…ALA is a medium chain fatty acid, naturally derived from plants and animals, Ref. [ 76 ] with potential antioxidant action and effective in the management of microvascular complications in diabetic rats, such as neuropathy, retinopathy, and other vascular disease [ 33 ]. The Neurological Assessment of Thioctic Acid in Diabetic Neuropathy trial (NATHAN) 1, the longest and largest multi-center, randomized, double-blind, parallel-group trial in patients with uncontrolled diabetes and DPN, showed a favorable effect of a daily dose of 600 mg ALA orally for four years on neuropathic symptoms but not in conduction velocity [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALA is a medium chain fatty acid, naturally derived from plants and animals, Ref. [ 76 ] with potential antioxidant action and effective in the management of microvascular complications in diabetic rats, such as neuropathy, retinopathy, and other vascular disease [ 33 ]. The Neurological Assessment of Thioctic Acid in Diabetic Neuropathy trial (NATHAN) 1, the longest and largest multi-center, randomized, double-blind, parallel-group trial in patients with uncontrolled diabetes and DPN, showed a favorable effect of a daily dose of 600 mg ALA orally for four years on neuropathic symptoms but not in conduction velocity [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…A couple of available cardiac therapies are dietary supplementation of α-lipoic acid (ALA) and cardiac resynchronization therapy (CRT). ALA, an enzymatic cofactor involved in energy production and mitochondrial biogenesis, has antioxidant and anti-inflammatory properties [ 33 ]. Dietary supplementation of ALA in two mouse models for human atherosclerosis exhibited significant reduction in atherosclerotic lesion formation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed mechanism of apoptosis and cell death induced by ALA is its remarkable antioxidant effect, accompanied with the ROS scavenging effect, observed in breast cancer cell lines [17,65]. As previously stated, increased production of ROS has been recognised in cancer cell progression due to an increased rate of cell division, metabolic activity and malfunction of intrinsic antioxidant [17,48,65,70]. It was also reported that ALA induced autophagy via inhibition of O6-methylguanine-DNA methyltransferase (MGMT) protein, which consequently led to apoptosis and cytotoxicity to chemo-resistant colorectal cancer cells [71,72].…”
Section: Roles Of Ascorbic Acid (Aa) and Alpha Lipoic Acid (Ala) In Cmentioning
confidence: 92%
“…Previous studies showed that the intercellular redox balance is linked with the cellular growth and plays a critical role in carcinogenesis. ALA was proposed to reduce elevated oxidative stress accumulated by cancerous cells, leading to apoptosis and inhibition of cell proliferation [45][46][47][48].…”
Section: Alpha-lipoic Acid (Ala)mentioning
confidence: 99%